HUBUNGAN ANTARA PENDEKATAN SUPERVISI YANG DIGUNAKAN PENGAWAS SEKOLAH DENGAN PELAKSANAAN PEMBELAJARAN GURU DI SMAN - Saleh, M. (Vidya Karya Jurnal Kependidikan, 2013)
The purpose of this study was to describe (1) the approach of supervision used by superintendent, (2) the level of working maturity of the Senior High School teachers in Banjarmasin, (3) the relevance of supervision approach used by superintendent, (4) the implementation of Senior High School teachers task in Banjarmasin, (5) the relationship between supervision approach used by superintendent and teachers tasks in Banjarmasin. The population of the study was a whole high school teachers in the city of Banjarmasin, while the sample is selected 186 teachers, with the characteristic of heve been working for over five years and have received supervision from the superintendent. Data were collected through questionnaires and analyzed using descriptive analysis techniques and simple correlation with point biserial correlation.The results showed: (1) non dorective is the most supervision approach used by superintendent, (2) the level of working maturity of high school teachers in Banjarmasin classified as very mature, (3) supervision approach used by superintendent in accordance with the level of working maturity of teachers who received supervision, (4) the implementation of teachers tasks are classified as good, (5) there is a positive and significant relationship between supervision approach used by the superintendent and teachersâ teaching duties.